Modified Hill Cipher: Secure Technique using Latin Square and Magic Square - Shibiraj, N; Tomba, I (International Journal of Computer Sciences and Engineering, 2018)
Hill cipher, the symmetric encryption algorithm based on linear matrix transformation is no longer used due to the vulnerability in security aspects. This paper aims to present the applicability of Latin squares and magic squares of odd order n in the encryption and decryption of Hill cipher. The pair of orthogonal diagonal Latin square (ODLS) of odd order and the magic square so derived are used for double encryption and double decryption in the modified Hill cipher to make the cryptosystem more secure. Different cipher text can be produced from a single diagonal Latin square (DLS) and diagraph letters are introduced in addition to the existing 26 letters of English alphabet to make the encryption and decryption possible for the modified Hill cipher.